2014
DOI: 10.1097/qad.0000000000000024
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 subtype C is not associated with higher risk of heterosexual HIV-1 transmission

Abstract: Background HIV-1 subtype C has emerged as the most prevalent strain of HIV-1 worldwide, leading to speculation that subtype C may be more transmissible than other subtypes. We compared the risk of HIV-1 transmission for subtype C versus non-C subtypes (A, D, G and recombinant forms) among heterosexual African HIV-1 serodiscordant couples. Methods We conducted a nested case-control analysis using data from two prospective cohort studies of heterosexual HIV-1 serodiscordant couples from 6 countries in eastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In Partners PrEP, 24% of HIV-positive partners had a viral load below 2,000 copies/mL at enrollment, 75 similar to other serodiscordant couple studies. 9,66,76 Surreptitious ART use has been noted in previous serodiscordant couple studies, but explains only a fraction (22%-33%) of the low viral loads. 66,77 Accordingly, the low viral load more likely reflects the selection of long-term sexual partners who have not transmitted HIV and who therefore may be less infectious.…”
Section: Evidence Of Prep Efficacy Against Sexual Exposure Outside Stmentioning
confidence: 90%
See 1 more Smart Citation
“…In Partners PrEP, 24% of HIV-positive partners had a viral load below 2,000 copies/mL at enrollment, 75 similar to other serodiscordant couple studies. 9,66,76 Surreptitious ART use has been noted in previous serodiscordant couple studies, but explains only a fraction (22%-33%) of the low viral loads. 66,77 Accordingly, the low viral load more likely reflects the selection of long-term sexual partners who have not transmitted HIV and who therefore may be less infectious.…”
Section: Evidence Of Prep Efficacy Against Sexual Exposure Outside Stmentioning
confidence: 90%
“…Regarding subtype C, ex vivo studies have shown that subtype C HIV isolates have higher transmission fitness compared to other group M isolates 61 and higher transmission efficiency across the cervical mucosa compared to subtype A isolates, 62 although Kahle et al did not report a difference in sexual transmissibility in subtype C versus nonsubtype C viruses. 66 Given that much of the work comparing sexual transmissibility of different HIV subtypes has been conducted among serodiscordant couples, who differ from the general population in multiple respects as discussed below, it remains an open question whether there are differences in sexual transmissibility of subtype C versus non-subtype C viruses in the general population.…”
Section: Evidence Of Prep Efficacy Against Sexual Exposure To Subtypementioning
confidence: 99%
“…Given this diversity, it is not surprising that natural (patient-derived) HIV-1 sequences also exhibit differences in their in vitro function, which may in turn influence viral pathogenesis. For example, it has been hypothesized that HIV-1 subtype C isolates, which comprise more than >50% of infections worldwide (Hemelaar, 2012), may be inherently more transmissible - possibly because of subtype-specific motifs within Env-gp120 that modulate interactions with host cell entry receptors (Walter et al, 2009) - though this remains controversial (Kahle et al, 2014). Subtype-specific differences in HIV-1 entry efficiency (Marozsan et al, 2005), replication capacity (Aralaguppe et al, 2016; Konings et al, 2006), and the function of viral accessory proteins Vif (Binka et al, 2012; Iwabu et al, 2010) and Nef (Mann et al, 2013) have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…CI values b 0.9 123 indicate a synergistic effect, 0.9 b CI b 1.1 indicate additive activity, 124 and CI N 1.1 indicates antagonism. 125 Tenofovir: clinical studies and efficacy as an HIV-1 microbicide 126 TFV is an adenosine NRTI with potent activity against 127 retroviruses, and it inhibits the synthesis of DNA by inserting 128 into propagating viral DNA. 31 Therefore, TFV prevents initial 94 The biological activity has been ascribed to 441 the cluster effects of randomly sulfated cellobiose, with an EC 50 442 of 3.2 μg/ml (Table 2).…”
mentioning
confidence: 99%